Complication rates of proximal hypospadias: meta-analyses of four surgical repairs. Issue 5 (October 2022) - Cousin, Ianis; Basmaison, Camille; Cousin, Elie; Lebonvallet, Nicolas; Germouty, Isabelle; Leven, Cyril; De Vries, Philine
Summary: Introduction: Proximal hypospadias surgery is impacted by a high complication rate. The goal of this work was to assess the overall composite complication rate, fistula rate and stenosis rate following proximal hypospadias surgery realized according to onlay urethroplasty, Duckett, Koyanagi and Bracka techniques. Methods: The databases MEDLINE, EMBASE, SCOPUS, Cochrane Library, the Cochrane Database of Systematic Reviews and the Cochrane Central Register of Controlled Trials (CENTRAL) and Sciencedirect were searched. Studies had to report data about the mean age of population, the average duration of patient follow-up and the number of procedures required for surgical treatment of primary and proximal hypospadias. Two independent including one urologist reviewers screened all the articles and selected the articles to be included. Results: Overall composite complication rates were 32%, 34%, 49%, and 43%, for Onlay urethroplasty, Duckett's tubularized flaps urethroplasty, Koyanagi repair and Bracka 2 stages repair, respectively. Fistula rates were 13%, 18%, 21% and 23% respectively. The heterogeneity of complication rates reported in the different studies was not moderated by age, country, or patient's continent origin. Discussion: The classifications of complications used in articles were disparate and make comparisons between techniques difficult. The report of post-surgical complications in the literature is often poorly coded and follow-up times were often too short. Conclusion: This meta-analysis attempts to determine to the extent possible, given the serious weaknesses in the hypospadias literature, plausible estimates of complication rates after skin flap urethroplasty. The patched onlay skin flap, the Duckett's tubularized skin flap technique, the Koyanagi's technique, and the Bracka's two-stage urethroplasty procedure lead to very high complication rates. Reported complication rates are comparable across techniques.